Chem-CRISPR/dCas9FCPF: a platform for chemically induced epigenome editing - Altinbay, Mukaddes; Wang, Jianhui; Chen, Jie; Schäfer, Daniel; Sprang, Maximilian; Blagojević, Biljana; Wölfl, Stefan; Andrade-Navarro, Miguel A; Dikic, Ivan; Knapp, Stefan; Cheng, Xinlai (Nucleic acids research, 2024)
Epigenetic aberration is one of the major driving factors in human cancer, often leading to acquired resistance to chemotherapies. Various small molecule epigenetic modulators have been reported. Nonetheless, outcomes from animal models and clinical trials have underscored the substantial setbacks attributed to pronounced on- and off-target toxicities. To address these challenges, CRISPR/dCas9 technology is emerging as a potent tool for precise modulation of epigenetic mechanism. However, this technology involves co-expressing exogenous epigenetic modulator proteins, which presents technical challenges in preparation and delivery with potential undesirable side effects. Recently, our research demonstrated that Cas9 tagged with the Phe-Cys-Pro-Phe (FCPF)-peptide motif can be specifically targeted by perfluorobiphenyl (PFB) derivatives. Here, we integrated the FCPF-tag into dCas9 and established a chemically inducible platform for epigenome editing, called Chem-CRISPR/dCas9FCPF. We designed a series of chemical inhibitor-PFB conjugates targeting various epigenetic modulator proteins. Focusing on JQ1, a panBET inhibitor, we demonstrate that c-MYC-sgRNA-guided JQ1-PFB specifically inhibits BRD4 in close proximity to the c-MYC promoter/enhancer, thereby effectively repressing the intricate transcription networks orchestrated by c-MYC as compared with JQ1 alone. In conclusion, our Chem-CRISPR/dCas9FCPF platform significantly increased target specificity of chemical epigenetic inhibitors, offering a viable alternative to conventional fusion protein systems for epigenome editing.